Soil microbial community structure and functionality changes in response to long‐term metal and radionuclide pollution. (20th January 2021) - Rogiers, Tom; Claesen, Jürgen; Van Gompel, Axel; Vanhoudt, Nathalie; Mysara, Mohamed; Williamson, Adam; Leys, Natalie; Van Houdt, Rob; Boon, Nico; Mijnendonckx, Kristel
Summary: Microbial communities are essential for a healthy soil ecosystem. Metals and radionuclides can exert a persistent pressure on the soil microbial community. However, little is known on the effect of long‐term co‐contamination of metals and radionuclides on the microbial community structure and functionality. We investigated the impact of historical discharges of the phosphate and nuclear industry on the microbial community in the Grote Nete river basin in Belgium. Eight locations were sampled along a transect to the river edge and one location further in the field. Chemical analysis demonstrated a metal and radionuclide contamination gradient and revealed a distinct clustering of the locations based on all metadata. Moreover, a relation between the chemical parameters and the bacterial community structure was demonstrated. Although no difference in biomass was observed between locations, cultivation‐dependent experiments showed that communities from contaminated locations survived better on singular metals than communities from control locations. Furthermore, nitrification, a key soil ecosystem process seemed affected in contaminated locations when combining metadata with microbial profiling. These results indicate that long‐term metal and radionuclide pollution impacts the microbial community structure and functionality and provides important fundamental insights into microbial community dynamics in co‐metal‐radionuclide contaminated sites.